Enhancing Trust and Market Presence of Butterfly Pea Flower Products through Halal and BPOM Certification: A Case Study of ASMAN TEMAN SETIA, Indonesia - Cindy Taurusta; Novia Ariyanti; Ferry Adhi Dharma; Puspitasari Putri Pambayun; Moch Ifan Fadilah Fadilah; Priyo Wahyu Setiyo Aji (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents a case study of ASMAN TEMAN SETIA, a local business group in Sawocangkring Village, Indonesia, specializing in producing various processed products from butterfly pea flowers. The study aims to improve public trust and market presence by obtaining Halal and BPOM certifications for their products. The research methodology involves collecting all necessary requirements for the certifications and registering them with the authorized authorities. The certified numbers are integrated into the product packaging for distribution through popular online marketplaces like Shopee and Tokopedia. The results reveal a significant increase in public trust, with the certified products garnering higher consumer confidence. The study also explores the potential of partnership and branding strategies, including registration on Google Business and Google Maps, to boost ASMAN TEMAN SETIA's popularity and facilitate accessibility for interested consumers. The implications of this research highlight the importance of certification in enhancing consumer confidence and expanding the market reach of local businesses, providing valuable insights for related professionals and stakeholders in the field of food product certification and marketing. Highlight: The study aims to compare wet cakes made from processed butterfly pea flower, ASMAN TEMAN SETIA, in Sawocangkring Village, Indonesia, after obtaining Halal and BPOM certifications. The implementation method involves collecting and fulfilling all requirements for Halal and BPOM permits and integrating the issued certificate numbers into the packaging design for distribution through online marketplaces like Shopee and Tokopedia, thereby increasing public trust. ASMAN TEMAN SETIA's registration on Google Business and Google Maps, along with strategic branding initiatives, leads to enhanced popularity not only for the business group but also for Desa Sawocangkring, benefiting the community's access to butterfly pea flower products. Keyword: Butterfly Pea Flower, Halal Certification, BPOM Certification, Online Marketplaces, Branding